Design of Physics Science for Early Childhood: Theoretical and Conceptual Framework of STEAM - Prastyaningrum, Ihtiari; Alfina, Alisa; Maharani, Swasti; Nugraha, Dewanta Arya (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
Good problem-solving will occur if children have good thinking skills and scientific knowledge. This scientific knowledge and thinking skills can be built through learning that integrates the concepts of literacy and STEAM. Physics is one form of science that can be used to develop the concepts of literacy and STEAM. This article aims to introduce activity designs that carry the concepts of literacy and STEAM, which can help early childhood students integrate science, technology, engineering, art, and mathematics to achieve certain targets. A more detailed concept of content that carries the concepts of literacy and STEAM is developed as a recommendation to education implementers. This concept design is based on the scene setting for early childhood. This study applies the 'most appropriate framework synthesis' approach, supported by interviews, in-depth observations, and literature reviews, to strengthen the conceptual framework in this study. The results of this study are a conceptual framework that refers to STEAM education but is more focused on the subject of physics. With a clear and completely structured conceptual framework, it is hoped that learning activities with the STEAM approach can run optimally and help stimulate cognitive, language, psychomotor, and social-emotional understanding in early childhood through the five STEAM disciplines.